Impressum - FMS (Scientific Journal Management in Sports, 2014)
Dear Sirs, In front of You is a new issue of “Management in Sport” - a scientifi c journal in the fi eld of management in sport. Publisher is the Faculty of Sport Alfa University in Belgrade. Th e journal is an important source of new scientifi c and technical information, as the only of its kind in the region. Th e editorial board of the journal is committed to upholding the reputation and the level of signifi cance of the magazine. Th e journal is published annually with the works to be published in Serbian and English. We invite all interested researchers in the fi eld of management in sport and other related fi elds associated with the sport to its scientifi c and technical projects contribute to the development of the magazine.